Similarity between the initial breakdown pulses of negative ground flash and narrow bipolar pulses - Ahmad, Mohd Riduan; Mohd Esa, Mona Riza; Cooray, Vernon (2014)
In the light of very recent proposal by Cooray et al. (2014), we believe that Narrow Bipolar Pulses (NBPs) event is a result of relativistic electron avalanches mechanism rather than conventional streamer-leader mechanism. Due to that, the close field change caused by the relativistic avalanches will not be preceded by any slow field change (e.g. Fig. 1) similar to the close field changes of return strokes where one can observe the field change caused by the leader prior the return stroke. In other word, the mechanism responsible for NBP does not contain pre-leader type activity. As put forward recently by Gurevich and Karashtin (2013) that the relativistic runaway breakdown (RB) could occur in the region between the main negative and lower positive charge (altitudes 5-6 km), we are motivated to investigate whether the initial field pulses of preliminary breakdown process (PBP) in close negative cloud-to-ground (CG) flashes are having similarity to the close NBPs. From 2 close negative CG flashes (less than 10 km) captured in 2012; one recorded on the November 23rd and the other one recorded on the November 27th (PBP train shown in Fig. 2), we observe that several initial field pulses (Figs. 2a and 2b) have similar characteristics to the close field NBPs with zero crossing time (ZCT) less than 5 μs and do not preceded by any slow field change. This is a strong indication that the mechanism responsible for those initial pulses is the same as NBP; that is relativistic RB avalanche. Furthermore, we observe that the subsequent field pulses following the initial field pulses (Fig. 2c) are preceded by slow field change, an indication that these subsequent field pulses are a result of streamer-leader mechanism.